Application of blockchain technique to reduce platelet wastage and shortage by forming hospital collaborative networks. Issue 2 (6th January 2021) - Rajendran, Suchithra
Abstract: Given the short shelf life of blood products and a decrease in donor population, hospitals endeavor to achieve an equilibrium between shortage and outdating. Though collaborating and sharing blood among hospitals will result in a reasonable reduction in surplus and deficit, health regulations strongly discourage blood exchange among hospitals due to traceability issues. With the recent advancement in peer-to-peer networking, blockchains have been used for record transactions in businesses with the advantage of being timestamped. This research is one of the first to address the blood inventory management problem using the blockchain technique by forming a collaborative network of hospitals and exchanging blood in that system, enabling transparency and traceability. A novel clustering technique, called multi-criteria clustering (MCC), using a mixed-integer programming approach, is proposed to form the blockchain network that bases its clustering decisions on a number of conflicting criteria, such as collaboration preference, geographical distribution, hospital size, and operational heterogeneity. Subsequent to this, a mathematical model is developed to identify purchasing strategies for each hospital in a blockchain network, given the opportunity to share blood among other hospitals in that network. This two-phase approach is tested using hospital settings in a neighborhood of a metropolitan city. Sensitivity analysis is performed to evaluate the effectiveness of the blockchain system with respect to change in cost, shelf life, demand distribution, and coefficient of demand variation. Based on the results, it can be concluded that, for all settings, the proposed blockchain network significantly outperforms the current system with independently acting hospitals, in spite of the additional blockchain development and operating expenses that are incurred.